Nanofiber micro-dispersed oxidized cellulose as a carrier for topical antimicrobials: first experience - Lochman, Petr; Plodr, Michal; Páral, Jiří; Šmejkal, Karel (Surgical infections, 2010)
BACKGROUND: Micro-dispersed oxidized cellulose, already used for hemostasis, might be helpful for introduction of an antimicrobial drug. AIM: To examine the effect of topically applied gentamicin attached to a new biodegradable carrier formed by micro-dispersed oxidized cellulose in microfiber and nanofiber form for treatment of acute wound infection and to assess the influence of this carrier on healing. MATERIALS AND METHODS: A model of a full-thickness infected dermal wound was created in 12 female domestic pigs. The effectiveness of topical gentamicin delivered with micro-dispersed oxidized cellulose carrier was tested in acute wound infections caused by Staphylococcus aureus, Pseudomonas aeruginosa, or Escherichia coli. RESULTS: The effectiveness of nanofiber micro-dispersed oxidized cellulose with gentamicin was proved according to culture findings. When assessed macroscopically, 100% of wounds treated by the nanofiber product had no signs of local infection. When microfiber micro-dispersed oxidized cellulose was used, cultures demonstrated residual bacteria in 94.4% of treated incisions despite the absence of clinically recognized infection. CONCLUSIONS: Micro-dispersed oxidized cellulose carrier with a sufficient concentration of an attached antibiotic appears to be effective for the treatment of full-thickness skin infections. The positive influence of the product on the healing of a dermal incision was shown, and a good hemostatic effect was confirmed.
Keywords: Animals; gentamiciny; Female; Anti-Infective Agents, Local; nanovlákna; Escherichia coli; výsledek terapie; ženské pohlaví; Wound Healing; Bacterial Infections; antiinfekční látky lokální; Drug Carriers; prasata; Nanofibers; Treatment Outcome; Gentamicins; infekce v ráně; Staphylococcus aureus; Administration, Topical; modely nemocí na zvířatech; aplikace lokální; Swine; Pseudomonas aeruginosa; hojení ran; Disease Models, Animal; celulosa oxidovaná; nosiče léků; zvířata; Wound Infection; Cellulose, Oxidized; bakteriální infekce